To solve the system by substitution, we can set the equations equal to each other:
-5x + 40 = 3x
Next, we can combine like terms:
-5x - 3x = -40
-8x = -40
Now, we can solve for x by dividing both sides by -8:
x = -40/-8
x = 5
Now that we have found the value of x, we can substitute it back into one of the original equations to solve for y. Let's use the equation y = 3x:
y = 3(5)
y = 15
Therefore, the solution to the system is x = 5 and y = 15.
Solve the system by substitution.
y, equals, minus, 5, x, plus, 40
y=
−5x+40
y, equals, 3, x
y=
3x
1 answer